The Computation of the Magnitude of the Far Field for an Eccentric Circular Cylinder - YILMAZ, BÜLENT (HINDAWI LTD, 2015)
The specific case of scattering of a plane wave by a two-layered penetrable eccentric circular cylinder has been considered and it is about the validity of the on surface radiation condition method and its applications to the scattering of a plane wave by a two-layered penetrable eccentric circular cylinder. The transformation of the problem of scattering by the eccentric circular cylinder to the problem of scattering by the concentric circular cylinder by using higher order radiation conditions, is observed. Numerical results presented the magnitude of the far field.
Keywords: SURFACE RADIATION CONDITION; SCATTERING